2021
DOI: 10.1042/cs20210207
|View full text |Cite
|
Sign up to set email alerts
|

Updates in deep learning research in ophthalmology

Abstract: Ophthalmology has been one of the early adopters of artificial intelligence (AI) within the medical field. Deep learning (DL), in particular, has garnered significant attention due to the availability of large amounts of data and digitized ocular images. Currently, AI in Ophthalmology is mainly focused on improving disease classification and supporting decision-making when treating ophthalmic diseases such as diabetic retinopathy, age-related macular degeneration (AMD), glaucoma and retinopathy of prematurity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 170 publications
0
21
0
Order By: Relevance
“…Despite the several advantages of using AI in ophthalmology, some limitations have been reported that create a serious challenge. These include higher accuracy in the training set than in the test set, which is called "overfitting" [1,80]; unfavorable results due to the use of irrelevant or inappropriate inputs, called "rubbish in and rubbish out" [1]; and the lack of transparency of decision-making and data analysis methods by the model, which is identified as a "black box" [1,80].…”
Section: Limitations Of Artificial Intelligencementioning
confidence: 99%
See 1 more Smart Citation
“…Despite the several advantages of using AI in ophthalmology, some limitations have been reported that create a serious challenge. These include higher accuracy in the training set than in the test set, which is called "overfitting" [1,80]; unfavorable results due to the use of irrelevant or inappropriate inputs, called "rubbish in and rubbish out" [1]; and the lack of transparency of decision-making and data analysis methods by the model, which is identified as a "black box" [1,80].…”
Section: Limitations Of Artificial Intelligencementioning
confidence: 99%
“…Therefore, it is necessary to validate a large dataset from a heterogeneous population that reflects real-world settings while observing medicolegal issues and ensuring data security [1,4]. Although there is a large amount of worldwide data available to design various AI-based models, data validity is an important issue [8,80]. Data should be verified by a specialist for quality and specific details related to the ocular structure, and manual data sorting is time-consuming.…”
Section: Limitations Of Artificial Intelligencementioning
confidence: 99%
“…In the United Kingdom (UK), around 1 in 9 people live with cardiovascular disease (CVD) [ 1 , 2 ]. A formal risk assessment tool, QRISK3, was developed using data from a cohort of 1.28 million individuals, and it is currently recommended by the National Institute for Health and Care Excellence (NICE) for CVD risk assessment and guidance for primary prevention strategies [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Artificial intelligence is capable of adapting to the rich ophthalmic medical image data characteristics [6] . The use of AI image recognition technology for ophthalmic medical image recognition, data extraction, and analysis [7] can significantly improve the efficiency of ophthalmic medical image recognition and reduce the workload of medical staff [8] . For pixel levels that ophthalmologists cannot recognize with naked eyes, artificial intelligence recognition technology can be used to carry out in-depth analysis [9] , improve the accuracy of ophthalmic medical diagnosis, and improve the efficiency and accuracy of ophthalmic medical image data identification and analysis work.…”
Section: Introductionmentioning
confidence: 99%